STUDI ADSORPSI ION FOSFAT OLEH BATU KAPUR BUKIT JIMBARAN - P. Suarya; A. A. B. Putra; N. L. P. Mahadewi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2020)
The presence of phosphate ions in the aquatic environment can cause disturbance of water balance, such as the increase of fertility of quatic plants resulting in water surface closure. Sunlight will be obstructed and the exchange of oxygen in water is also disrupted. Various attempts to remove phosphate ions have been carried out, adsorption is one of the promising alternative methods to reduce these ions from the waters because of the high effectiveness and the cost required for the preparation of the adsorbent is quite cheap. The general objective of this research was to study the selectivity of limestone in adsorpting phosphate ions. The results obtained can complement the data on the use of limestone which in turn can be used as a reference in the management of wastewater contaminated by phosphate ions. The ability of limestone in adsorping phosphate ions was tested using the Batch method with an investigation on the variations of the adsorption time and the concentration of phosphate ions. Limestone characterization test results before and after activation showed an increase in limestone characteristics as follows: surface acidity increased from 0.50 to 1.40 mmol/g and the specific surface area increased from 12.66 to 25.61 m2 /g. The amount of phosphate adsorped to the activated limestone at the optimum contact time of 15 minutes was of 3.125 mg/g, and at the concentration of 70 ppm was of 3.094 mg/g following the Langmuir adsorption isotherm pattern with an R2 value of 0.9981. Keywords: activation, adsorption, characterization, limestone, phosphate ion